Blue Light Deprivation Produces Depression-Like Responses in Mongolian Gerbils - Hu, Hong; Kang, Chenping; Hou, Xiaohong; Zhang, Qi; Meng, Qinghe; Jiang, Jianjun; Hao, Weidong (Frontiers in Psychiatry, 2020)
Background: Depression is a leading cause of disability worldwide and is a major contributor to the overall global burden of disease, but its etiology is poorly understood. It has been reported that a disrupted biological rhythm, in terms of a shortened light duration and total darkness, can cause depression-like behaviors in animals. Blue light was reported to have an inhibitory effect on melatonin, which is considered an important clock rhythm biomarker. In the present study, we investigated the effects of blue light deprivation on depressive-like behaviors in gerbils and explored the underlying mechanisms. Methods: Gerbils were housed under white light with a filter to block the blue light or without a filter. The behaviors of the gerbils were observed. The biological rhythm, 5-HT, hypothalamic-pituitary-adrenal (HPA) axis and melanopsin pathway were analyzed. Results: We found that blue light deprivation (BLD) induced depression-like behavior in gerbils. Melatonin lost its rhythm, and corticosterone (CORT) levels decreased in the morning in the BLD group. Lower corticotropin-releasing hormone (CRH) in the hypothalamus and lower adrenocorticotropin hormone (ACTH)/CORT in serum were observed after BLD. Furthermore, 5-HT in the serum and brain were decreased after BLD. Additionally, BLD affected the blue light sensitivity protein melanopsin and its pathway, with downregulation of the proteins melanopsin, PKCα, and c-Fos and the mRNA levels of c-fos and trpc3 and upregulation of the protein p-PKCα. Conclusions: Our findings indicated that BLD might produce depression-like behaviors in gerbils. Melatonin arrhythmicity, HPA axis abnormalities, 5-HT decreases and melanopsin pathway changes might be associated with the depression behavioral phenotype in gerbils.